Effect of alirocumab on coronary plaque in patients with coronary artery disease assessed by optical coherence tomography - Fei Gao; Zhi Jian Wang; Xiao Teng Ma; Hua Shen; Li Xia Yang; Yu Jie Zhou (Lipids in Health and Disease, 2021)
Abstract Background Proprotein convertase subtilisin kexin type 9 (PCSK9) inhibitors have been demonstrated to produce significantly greater reduction in LDL cholesterol levels and cardiovascular events than standard statin therapy. However, evidence on the impact of PCSK9 inhibitors on coronary plaque composition and morphology is limited. Methods In this open-label randomized study, eligible patients with intermediate coronary lesions and elevated LDL cholesterol values were randomized to either alirocumab 75 mg Q2W plus statin (atorvastatin 20 mg/day or rosuvastatin 10 mg/day) therapy or standard care. Optical coherence tomography (OCT) assessments for target lesions were obtained at baseline and at 36 weeks of follow-up. Results LDL cholesterol levels were significantly decreased in both the alirocumab and standard care arms, whereas the absolute reduction in LDL cholesterol was significantly greater in patients treated with alirocumab (1.72 ± 0.51 vs. 0.96 ± 0.59, P < 0.0001). Compared with standard care, the addition of alirocumab to statins was associated with significantly greater increases in minimum fibrous cap thickness (18.0 [10.8–29.2] μm vs 13.2 [7.4–18.6] μm; P = 0.029), greater increases in minimum lumen area (0.20[0.10–0.33] mm2 vs 0.13 [0.12–0.24] mm2; P = 0.006) and a greater diminution in maximum lipid arc (15.1̊ [7.8–24.5] vs. 8.4̊ [2.0–10.5]; P = 0.008). Conclusions The addition of alirocumab to statins can not only provide additional LDL cholesterol lowering effects but also have a potential role in promoting a more stable plaque phenotype. Trial registration ClinicalTrials.gov Identifier: NCT04851769 . Registered 2 Mar 2019.